1992
DOI: 10.1017/s0003598x00081023
|View full text |Cite
|
Sign up to set email alerts
|

Repton and the Vikings

Abstract: In 873 the Viking Great Army took winter quarters at the Anglo-Saxon monastery of Repton in the heart of Mercia. Excavations 1974–88 found their D-shaped earthwork on the river bank, incorporated in the stone church. Burials of Viking type were made at the east end of the church, and an existing building was cut down and converted into the chamber of a burial mound containing at least 249 individuals. Here is a first account of the evidence for the Vikings at Repton in and after the campaigning season of 873-4. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 10 publications
0
31
0
1
Order By: Relevance
“…Some of these individuals have been subjected to isotope analysis, which has suggested that they were migrants, and possibly from Scandinavia (Budd et al . ; Speed and Walton Rogers ,).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these individuals have been subjected to isotope analysis, which has suggested that they were migrants, and possibly from Scandinavia (Budd et al . ; Speed and Walton Rogers ,).…”
mentioning
confidence: 99%
“…; Richards ); at this time, cremation is an intrusive rite in England but was practised in Sweden, Norway and northern Jutland. Other contenders for Scandinavian identity include isolated accompanied burials such as that of a woman buried with Scandinavian artefacts at Adwick‐le‐Street, South Yorkshire (Speed and Walton Rogers ,), barrow burials with Scandinavian grave goods, e.g. Bedale and Camphill, both North Yorkshire (see below), and burials within churchyards that contain distinctively Scandinavian artefacts, for example the burial containing many grave goods including a Scandinavian sword and a silver pendant in the shape of Thor's hammer at Repton, Derbyshire (Biddle and Kjølbye‐Biddle 1992; 2001).…”
mentioning
confidence: 99%
“…189 The most obvious 'Viking' is the warrior aged at least 35 -45 (Grave 511), buried immediately to the north of the chancel, within the defended enclosure. A second male, aged 17 to 20 (Grave 295), buried soon after and adjacent to the warrior, has been interpreted as his weapon bearer.…”
mentioning
confidence: 99%
“…Clearly some burial groups in Britain and Ireland, such as those with predominantly or completely male interments at the grave-field in South Great Georges Street, Dublin (O'Donovan 2008, Simpson 2005, Heath Wood, Ingleby , Repton (Biddle and Kjølbye-Biddle 1992), Oxford (Pollard et al 2012), and Weymouth (Chenery et al 2014 [this volume]), are not cemeteries normally associated with settlement. The presence and cultural impact of these individuals on the surrounding populations may have been fleeting.…”
Section: Contextmentioning
confidence: 99%